MODEL ANALISIS DYNAMIC LIMBAH MEDIS RUMAH SAKIT DI DENPASAR BALI - Maulidiyah Nurma Alfiyanti; Ni Made Utami Dwipayanti; I Made Sara Wijana (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2023)
Denpasar has 18 hospitals, 11 health centers, and 25 sub-health centers located at South Denpasar, East Denpasar, West Denpasar, and North Denpasar (Dinkes, 2020). The average medical waste generated every day is 1800 kg/day or 1.8 tons day (DLHK, 2018). The methods to develop solid medical waste management include minimizing medical waste from its source, sorting, storing, reusing and recycling, collecting, transporting, storing, processing, and destroying it (Health Ministry of the Republic of Indonesia, 2018). Dynamic analysis is the right approach to examine a complex problem with limited data. This research uses quantitative and qualitative based on primary and secondary data. Research where located in 15 public hospitals in Denpasar City. The time of research starts in November – December 2021 with a prediction period of 10 years until 2030. According to the result he weight of solid medical waste increased from year to year. In 2022 the weight of medical waste was redicted to reach 727.75 kg or 730 tons. The weight of solid medical waste becomes 436.136 kg or 436 tons with a 40% reduction policy implemented in its entirety. The cost aspect of simulation without hospital policy will cost more than IDR 9 billion per year. The proposed solution to maximize the combination of solid medical waste reduction and management policies in Bali. These efforts can minimize costs and reduce the production of solid medical waste from source to utilization. Keywords: Dynamic Analysis Model, Technical Aspect, Hospital, Medical Waste